Chinese Domestic Politics and Foreign Policy in the 1970s - Whiting, Allen S. (Michigan Monographs In Chinese Studies, 2020)
Chinese Domestic Politics and Foreign Policy in the 1970s undertakes a systematic examination of selected aspects of Peking's foreign policy, using content analysis, both quantitative and qualitative, of the media. The first study treats media images of the United States and Taiwan in 1976-77; the second analyzes domestic politics and foreign trade, 1971-1976. [1, 2]